2005
DOI: 10.1002/anie.200500919
|View full text |Cite
|
Sign up to set email alerts
|

Pt-Cu Core-Shell and Alloy Nanoparticles for Heterogeneous NOx Reduction: Anomalous Stability and Reactivity of a Core-Shell Nanostructure

Abstract: Cores to celebrate: At 370 °C, Pt@Cu core–shell nanoparticles rapidly alloy but the reciprocal core–shell nanoparticles, Cu@Pt (see STEM images, left: Cu spectral map; middle: Pt spectral map; right: bright‐field image), are kinetically stabilized and show high activity and selectivity for NO reduction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
161
0
3

Year Published

2009
2009
2019
2019

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 237 publications
(169 citation statements)
references
References 24 publications
(27 reference statements)
4
161
0
3
Order By: Relevance
“…Eichhorn and co-workers demonstrated that, although γ -Al 2 O 3 supported Cu@Pt core/shell nanoparticles have high catalytic activity for NO reduction equal to that of pure Pt nanoparticles, the novel bimetallic core/shell nanocatalysts show signifi cantly greater selectivity for N 2 formation. [ 101 ] More excitedly, noble metal-based catalysts can be completely replaced by non-precious metal alloy catalysts in some cases. Studt et al performed DFT calculations to identify relations in heats of adsorption of hydrocarbon molecules and fragments on metal surfaces and suggested that Ni-Zn alloys might be alternatives for selective hydrogenation of acetylene instead of Pd-Ag catalysts which are mostly used in modern industry.…”
Section: Heterogeneous Catalysismentioning
confidence: 99%
“…Eichhorn and co-workers demonstrated that, although γ -Al 2 O 3 supported Cu@Pt core/shell nanoparticles have high catalytic activity for NO reduction equal to that of pure Pt nanoparticles, the novel bimetallic core/shell nanocatalysts show signifi cantly greater selectivity for N 2 formation. [ 101 ] More excitedly, noble metal-based catalysts can be completely replaced by non-precious metal alloy catalysts in some cases. Studt et al performed DFT calculations to identify relations in heats of adsorption of hydrocarbon molecules and fragments on metal surfaces and suggested that Ni-Zn alloys might be alternatives for selective hydrogenation of acetylene instead of Pd-Ag catalysts which are mostly used in modern industry.…”
Section: Heterogeneous Catalysismentioning
confidence: 99%
“…Dealloyed Pt-Cu core-shell nanoparticles were prepared by selective dissolution of Cu atoms from nanoparticle surfaces and have demonstrated surface catalytic improvement towards oxygen reduction [12,13]. It was proposed that a reduced Pt-Pt distance near the particle surface stabilized by the lattice contracted alloy core might be responsible for the surface catalytic reactivity.…”
Section: Introductionmentioning
confidence: 99%
“…However, each kind of metal magnetic nanoparticles has its intrinsic properties and usually can be used only in a specified frequency range. To meet the above requirements, the development of composite metal nanoparticles which combine two or more components in each individual particle to modify the bulk properties [6][7][8][9][10][11] or the surface properties may be an efficient strategy [12][13][14][15][16][17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%